Antimicrobial and anti-caries effects of 4% titanium tetrafluoride varnish under a microcosm biofilm model on dentin - Santos, Daiana Moreli Soares dos (2018)
The study aimed: 1) to compare the effect of two different nutrients supply models (static and semi-dynamic) on the microcosm biofilm viability and dentin carious lesions formation; 2) to compare micro-CT versus TMR to measure dentin demineralization; and 3) to evaluate the effect of 4% TiF4 varnish on the viability and metabolism of a microcosm biofilm and on development of dentin carious lesions. Microcosm biofilm was produced using pooled human saliva mixed with McBain saliva for the first 8 h; thereafter, only McBain saliva with 0.2% sucrose was applied daily (37°C, 5% CO2), for a total time of 5 days. In the study 1, the static model consisted of 24-wells microplate, where bovine root dentin samples were submitted to biofilm formation. The semi-dynamic model, consisted of artificial mouth with continuous flow of McBain saliva with 0.2% sucrose (0.15 ml/min, 37°C) during 10 h a day (for the other 14 h, no flow was applied). Biofilm viability was measured by fluorescence and dentin demineralization by TMR. For the studies 2 and 3, bovine root dentin samples were treated for 6 h: A) 4% TiF4 (pH 1.0, 2.45% F); B) 5.42% NaF (pH 5.0, 2.45% F); C) 2% CHX gel positive control D) placebo or E) untreated negative control. Treated samples were submitted to biofilm formation under static model as described above. Demineralization was measured using micro-CT (study 2) and TMR (studies 2 and 3). In the study 3, biofilm was analyzed with respect to viability by fluorescence and CFU counting for total microorganisms, total streptococci, mutans streptococci and Lactobacillus sp., and lactic acid and EPS production. In study 1, biofilm viability was lower for the static model (0.420±0.138) compared to semi-dynamic one (0.944±0.599). Both models were able to provoke dentin demineralization; however, the static model produced a higher number of typical subsurface lesions (83%) compared to the semi-dynamic (45%). In study 2, both fluorides were able to reduce dentin demineralization. Data obtained from micro- CT and TMR presented a significant and positive correlation (Z: r=0.78 p<0.0001 and LD: r=0.57 p<0.0001) In study 3, all treatments reduced the biofilm viability, but not the CFU counting, except NaF that significantly reduced the number of Lactobacillus sp. compared to control. No treatment was able to decrease the lactic acid production neither EPS production, except CHX that reduced the amount of insoluble EPS. Fluorides were able to reduce dentin demineralization compared to control, but TiF4 had the best effect in reducing mineral loss and lesion depth (reduction of Z: 70% and LD: 45%). In conclusion, 1) the nutrient supply model may have influence on the biofilm viability and the profile of dentin carious lesions; 2) micro-CT may be a suitable non-destructive method to measure dentin demineralization; and 3) despite TiF4 varnish has no relevant antimicrobial effect, it is the best option to reduce the development of dentin carious lesions under this model.